The Nexus Between Microfinance & Sustainable Development: Examining The Regulatory Changes Needed For Its Efficient Implementation. - Ramaswamy, Apoorva; Krishnamoorthy, Aditya (European Journal of Sustainable Development, 2016)
Micro-Finance as a concept has been largely hit or miss in it’s implementation. While Mohammed Yousuf helped launch the concept into the mainstream in the early 2000’s, the use of Microfinance as a means of achieving Sustainable Development has gained traction only in recent years. The aim of this paper is to analyze the regulatory changes which are required in order to ensure that Microfinance Institutions function efficiently, in order to contribute to Sustainable Development in India. Through the course of this paper, the authors will examine a variety of Microfinance models in order, to comprehend their impact on Sustainable Development. For this purpose, the authors will conduct quantitative and qualitative analysis of various stakeholders in the field of Microfinance and examine a number of successful Microfinance models from other developing nations, to assess the various challenges and issues faced by these institutions. Through the outcome of this analysis, the authors will seek to understand the regulatory status quo & the lacunae prevailing in the law and will thereby seek to arrive at solutions, in order to successfully implement Microfinance as a means to Sustainable Development in India. Key Words: Microfinance, Sustainable, Development, Regulation, India, Qualitative, Stakeholder